2023
DOI: 10.1177/14653125231203743
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for treatment planning and soft tissue outcome prediction of orthognathic treatment: A systematic review

Daisy Salazar,
Paul Emile Rossouw,
Fawad Javed
et al.

Abstract: Background: The accuracy of artificial intelligence (AI) in treatment planning and outcome prediction in orthognathic treatment (OGT) has not been systematically reviewed. Objectives: To determine the accuracy of AI in treatment planning and soft tissue outcome prediction in OGT. Design: Systematic review. Data sources: Unrestricted search of indexed databases and reference lists of included studies. Data selection: Clinical studies that addressed the focused question ‘Is AI useful for treatment planning and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These limitations stem from the lack of strict guidelines, which results in a heavy reliance on expert decisions and opinions. A systematic review conducted by Smith et al [154] further supports this notion by indicating that the results of current studies cannot be easily generalized due to their significant heterogeneity. The authors carefully concluded that AI might be a useful tool in planning orthognathic surgery.…”
Section: Orthognathic Surgery Decision Making and Planningmentioning
confidence: 69%
See 1 more Smart Citation
“…These limitations stem from the lack of strict guidelines, which results in a heavy reliance on expert decisions and opinions. A systematic review conducted by Smith et al [154] further supports this notion by indicating that the results of current studies cannot be easily generalized due to their significant heterogeneity. The authors carefully concluded that AI might be a useful tool in planning orthognathic surgery.…”
Section: Orthognathic Surgery Decision Making and Planningmentioning
confidence: 69%
“…This leads to a heavy dependence on expert decisions and opinions. A systematic review by Smith et al [154] further highlighted the significant heterogeneity among current studies and the difficulty in generalizing their results. The authors cautiously concluded that AI could be a valuable tool in orthognathic surgery planning, but further research is necessary.…”
Section: Orthognathic Surgery Decision Making and Planningmentioning
confidence: 99%